Evaluation of Mangosteen Peel Extract as a Substitute for Eosin 2% in Ascaris lumbricoides Egg Staining - Nastiti, Hilari Rio Rosa; Widiyanto, SY Didik; Rosidah, Umi; Rokhani, Latifah Intan; Wahyuni, Sri; Handayani, Sih Rini (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Parasitic helminth infections remain a major public health problem in Indonesia, particularly among school-aged children. Tropical climatic conditions contribute to the high prevalence of Ascaris lumbricoides infection in endemic areas. Microscopic examination of helminth eggs commonly uses synthetic dyes such as eosin 2%; however, synthetic stains may pose potential health and environmental risks. This study aimed to evaluate the potential of mangosteen peel extract from Purbalingga (Garcinia mangostana L.) as a natural alternative stain for A. lumbricoides eggs. Mangosteen peel extract was tested at concentrations of 50%, 65%, and 80%, with eosin 2% used as a control. Staining quality was evaluated comparatively based on background contrast and clarity of egg morphology. The results showed that extract concentrations of 50% and 65% produced suboptimal visualization of A. lumbricoides eggs, whereas the 80% concentration provided better staining quality and clearer egg morphology, comparable to eosin 2%. Post hoc analysis demonstrated a significant difference between the eosin 2% control and the 50% extract concentration (p-value <0,001), while no significant differences were observed between eosin 2% and the 65% (p-value = 0,571) or 80% (p-value = 1,000) extract concentrations. These findings indicate that mangosteen peel extract at an 80% concentration has potential as a natural alternative stain to assist microscopic visualization of A. lumbricoides eggs. However, further studies are required to evaluate the reproducibility and chemical stability of the extract before its broader application in diagnostic parasitology laboratories.